Penyuluhan Keluarga Berencana (KB) Tentang Pemilihan Alat Kontrasepsi pada Wanita Usia Subur (WUS) di Dusun I Desa Nunkurus - Ninick Corea Fernandez; Ermi Lilianda Alang (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
Women of Childbearing Age (WUS) have an important role in the success of the Family Planning (KB) program. However, there are still many WUS who experience limited information regarding the types of contraceptives, so that WUS quite often choose the wrong or even afraid to use KB. Therefore, KB Counseling carried out in the form of community service aims to maximize the understanding and awareness of women of childbearing age in order to increase the use of KB and in choosing the right, safe, and appropriate contraceptives according to the health conditions and reproductive plans of WUS. This counseling was held on December 10, 2025, which took place in Dusun I Nunkurus. This activity was attended by 20 WUS. The methods used in this activity included interactive lectures using media (Leaflets and PPT), question and answer discussions, and simulations of introducing contraceptives (injectable KB, pills, implants, IUDs, and condoms). Evaluation of this level of knowledge was carried out using questions and answers on WUS and there was a significant increase in knowledge, where 85% of WUS managed to understand the advantages and disadvantages of each contraceptive. Furthermore, several women who were previously hesitant about using family planning began to show interest in switching to contraceptive methods. Therefore, it can be concluded that this family planning education activity has proven effective in increasing women's knowledge regarding contraceptive selection and has had a positive impact on women in the local area.